2016
DOI: 10.1017/s000711451500032x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of diet on the physical and mental development of children: views of parents and teachers in four European countries

Abstract: Although the impact of diet on physical health is an important public health issue, less attention has been devoted to the relationship between nutrition and children's mental development. The views of parents and teachers about the extent to which diet affects physical and mental development of children were compared in four European countries. An online questionnaire (developed in English and translated) was circulated through a market research agency. Participants were parents or teachers of children aged 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Children’s diet plays a crucial role in their health, growth, development, mental and physical performance, and emotional well-being [ 1 ]. To understand nutritional needs and their potential impact on health, healthy eating patterns can be simply described as those rich in health-promoting foods, including plant-based foods, fresh vegetables and fruits, nuts, sources of omega-3 fatty acids, and products low in saturated fats and trans-fats, animal-derived proteins, and added/refined sugars [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Children’s diet plays a crucial role in their health, growth, development, mental and physical performance, and emotional well-being [ 1 ]. To understand nutritional needs and their potential impact on health, healthy eating patterns can be simply described as those rich in health-promoting foods, including plant-based foods, fresh vegetables and fruits, nuts, sources of omega-3 fatty acids, and products low in saturated fats and trans-fats, animal-derived proteins, and added/refined sugars [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Eating patterns of children were associated with maternal eating and sedentary habits [ 24 ]. Relationships between parents’ diet and lifestyle and those of their children and adolescents were scarcely described in European countries, but not in Spain yet [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In making food choices for their children, research has shown that parents are aware of the importance of developing good eating habits for long-term health and are concerned with balancing a healthy diet with their child’s food preferences ( 3 ) . Even though parents associate some foods (such as sugary drinks) with effects on mood and behaviour ( 4 ) , most perceive that diet has a stronger impact on the physical development of their child than on his/her mental performance ( 5 ) . Food and nutrition, however, have important and pervasive impacts on brain development and cognitive functioning through effects on cell structure, neurotransmission, energy supply to the brain and metabolism ( 6 , 7 ) .…”
mentioning
confidence: 99%